ATF4 Protects the Heart From Failure by Antagonizing Oxidative Stress. Issue 1 (16th May 2022) - Wang, Xiaoding; Zhang, Guangyu; Dasgupta, Subhajit; Niewold, Erica L.; Li, Chao; Li, Qinfeng; Luo, Xiang; Tan, Lin; Ferdous, Anwarul; Lorenzi, Philip L.; Rothermel, Beverly A.; Gillette, Thomas G.; et al.
Abstract : Background: Cellular redox control is maintained by generation of reactive oxygen/nitrogen species balanced by activation of antioxidative pathways. Disruption of redox balance leads to oxidative stress, a central causative event in numerous diseases including heart failure. Redox control in the heart exposed to hemodynamic stress, however, remains to be fully elucidated. Methods: Pressure overload was triggered by transverse aortic constriction in mice. Transcriptomic and metabolomic regulations were evaluated by RNA-sequencing and metabolomics, respectively. Stable isotope tracer labeling experiments were conducted to determine metabolic flux in vitro. Neonatal rat ventricular myocytes and H9c2 cells were used to examine molecular mechanisms. Results: We show that production of cardiomyocyte NADPH, a key factor in redox regulation, is decreased in pressure overload-induced heart failure. As a consequence, the level of reduced glutathione is downregulated, a change associated with fibrosis and cardiomyopathy. We report that the pentose phosphate pathway and mitochondrial serine/glycine/folate metabolic signaling, 2 NADPH-generating pathways in the cytosol and mitochondria, respectively, are induced by transverse aortic constriction. We identify ATF4 (activating transcription factor 4) as an upstream transcription factor controlling the expression of multiple enzymes in these 2 pathways. Consistently, joint pathway analysis of transcriptomic and metabolomic data reveal that ATF4 preferably controls oxidative stress and redox-related pathways. Overexpression of ATF4 in neonatal rat ventricular myocytes increases NADPH-producing enzymes‚ whereas silencing of ATF4 decreases their expression. Further, stable isotope tracer experiments reveal that ATF4 overexpression augments metabolic flux within these 2 pathways. In vivo, cardiomyocyte-specific deletion of ATF4 exacerbates cardiomyopathy in the setting of transverse aortic constriction and accelerates heart failure development, attributable, at least in part, to an inability to increase the expression of NADPH-generating enzymes. Conclusions: Our findings reveal that ATF4 plays a critical role in the heart under conditions of hemodynamic stress by governing both cytosolic and mitochondrial production of NADPH.